Development of top-oil temperature thermal models for transformer - Roslan, Muhammad Hakirin (2017)
Hot-Spot Temperature (HST) is defined as the highest temperature inside a transformer and can be determined based on the numerical network thermal model. In this approach, Top-Oil Temperature (TOT) is among the crucial components to obtain reliable HST. Currently, there are two loading guides that utilize the numerical network thermal model in order to obtain the TOT which are IEC 60076-7 and IEEE C57.91-1995. Other types of TOT numerical network thermal model are based on the thermal-electrical analogy method. There are several improvements that can be applied to existing TOT models such as reducing the complexity of the models and increasing the accuracy which is the main motivation of this study. The main aim of this research is to provide alternative approaches to obtain the TOT of transformers. Two TOT thermal models were proposed in this study named as Thermal Model 1 (TM1) and Thermal Model 2 (TM2). These models were developed based on the proposed concept of pathway of energy transfer. . TM1 was developed based on redefinition of nonlinear thermal resistance through approximation of convection coefficient, h. Meanwhile, TM2 was developed based on the concept of nonlinearity of thermal resistance of which the oil time constant was embedded in the model in order to improve the accuracy. The performance of the TM1 and TM2 were evaluated based on measured TOT with constant loadings from 7 transformers with either ONAN or ONAF cooling modes. Both TM1 and TM2 were also tested on a transformer with step loading. The performances of TM1 and TM2 were analyzed through comparison with previous Thermal-Electrical (namely as TE1 and TE2), Exponential (IEC 60076-7) and Clause 7 (IEEE C57.91-1995) TOT thermal models. Under constant loading, both TM1 and TM2 perform relatively well compare to TE1 and TE2 models. The performance of TM1 and TM2 are even better than Exponential and Clause 7 models to represent the measured TOT. The highest maximum and Root Mean Square (RMS) errors for TM1 are 6.66 °C and 2.76 °C while TM2 has the highest maximum and RMS errors of 6.24 °C and 2.58 °C respectively. Both TM1 and TM2 could represent the measured TOT quite well under step loading. The simulated TOT for TM1 and TM2 are quite close to TE1 and close to measured TOT. The highest maximum and RMS errors for both TM1 and TM2 are 5.77 °C and 2.02 °C respectively.Hot-Spot Temperature (HST) is defined as the highest temperature inside a transformer and can be determined based on the numerical network thermal model. In this approach, Top-Oil Temperature (TOT) is among the crucial components to obtain reliable HST. Currently, there are two loading guides that utilize the numerical network thermal model in order to obtain the TOT which are IEC 60076-7 and IEEE C57.91-1995. Other types of TOT numerical network thermal model are based on the thermal-electrical analogy method. There are several improvements that can be applied to existing TOT models such as reducing the complexity of the models and increasing the accuracy which is the main motivation of this study. The main aim of this research is to provide alternative approaches to obtain the TOT of transformers. Two TOT thermal models were proposed in this study named as Thermal Model 1 (TM1) and Thermal Model 2 (TM2). These models were developed based on the proposed concept of pathway of energy transfer. . TM1 was developed based on redefinition of nonlinear thermal resistance through approximation of convection coefficient, h. Meanwhile, TM2 was developed based on the concept of nonlinearity of thermal resistance of which the oil time constant was embedded in the model in order to improve the accuracy. The performance of the TM1 and TM2 were evaluated based on measured TOT with constant loadings from 7 transformers with either ONAN or ONAF cooling modes. Both TM1 and TM2 were also tested on a transformer with step loading. The performances of TM1 and TM2 were analyzed through comparison with previous Thermal-Electrical (namely as TE1 and TE2), Exponential (IEC 60076-7) and Clause 7 (IEEE C57.91-1995) TOT thermal models. Under constant loading, both TM1 and TM2 perform relatively well compare to TE1 and TE2 models. The performance of TM1 and TM2 are even better than Exponential and Clause 7 models to represent the measured TOT. The highest maximum and Root Mean Square (RMS) errors for TM1 are 6.66 °C and 2.76 °C while TM2 has the highest maximum and RMS errors of 6.24 °C and 2.58 °C respectively. Both TM1 and TM2 could represent the measured TOT quite well under step loading. The simulated TOT for TM1 and TM2 are quite close to TE1 and close to measured TOT. The highest maximum and RMS errors for both TM1 and TM2 are 5.77 °C and 2.02 °C respectively. It can be summarized that both TM1 and TM2 can be used as an alternative approach to determine the TOT with less input parameter and reasonable accuracy as compared to previous TOT thermal models.